Q fever in Spain: Description of a new series, and systematic review. - Vanesa Alende-Castro; Cristina Macía-Rodríguez; Ignacio Novo-Veleiro; Xana García-Fernández; Mercedes Treviño-Castellano; Sergio Rodríguez-Fernández; Arturo González-Quintela (PLoS Neglected Tropical Diseases, 2018)
Background Forms of presentation of Q fever vary widely across Spain, with differences between the north and south. In the absence of reported case series from Galicia (north-west Spain), this study sought to describe a Q-fever case series in this region for the first time, and conduct a systematic review to analyse all available data on the disease in Spain. Methods Patients with positive serum antibodies to Coxiella burnetii from a single institution over a 5-year period (January 2011-December 2015) were included. Patients with phase II titres above 1/128 (or documented seroconversion) and compatible clinical criterial were considered as having Q fever. Patients with clinical suspicion of chronic Q-fever and IgG antibodies to phase I-antigen of over 1/1024, or persistently high levels six months after treatment were considered to be cases of probable chronic Q-fever. Systematic review: We conducted a search of the Pubmed/Medline database using the terms: Q Fever OR Coxiella burnetii AND Spain. Our search yielded a total of 318 studies: 244 were excluded because they failed to match the main criteria, and 41 were discarded due to methodological problems, incomplete information or duplication. Finally, 33 studies were included. Results A total of 155 patients, all of them from Galicia, with positive serological determination were located during the study period; 116 (75%) were deemed to be serologically positive patients without Q fever and the remaining 39 (25%) were diagnosed with Q fever. A potential exposure risk was found in 2 patients (5%). The most frequent form of presentation was pneumonia (87%), followed by isolated fever (5%), diarrhoea (5%) and endocarditis (3%). The main symptoms were headache (100%), cough (77%) and fever (69%). A trend to a paucisymptomatic illness was observed in women. Hospital admission was required in 37 cases, and 6 patients died while in hospital. Only 2 patients developed chronic Q-fever. Systematic review: Most cases were sporadic, mainly presented during the winter and spring, as pneumonia in 37%, hepatitis in 31% and isolated fever in 29.6% of patients. In the north of Spain, 71% of patients had pneumonia, 13.2% isolated fever and 13% hepatitis. In the central and southern areas, isolated fever was the most frequent form of presentation (40%), followed by hepatitis (38.4%) and pneumonia (17.6%). Only 31.7% of patients reported risk factors, and an urban-environment was the most frequent place of origin. Overall mortality was 0.9%, and the percentage of patients with chronic forms of Q-fever was 2%. Conclusions This is the first study to report on a Q-fever case series in Galicia. It shows that in this region, the disease affects the elderly population -even in the absence of risk factors- and is linked to a higher mortality than reported by previous studies. While pneumonia is the most frequent form of presentation in the north of the country, isolated fever and hepatitis tend to be more frequent in the central and southern areas. In Spain, 32% of Q-fever cases do not report contact with traditional risk factors, and around 58% live in urban areas.